2015
DOI: 10.1080/14786419.2015.1043552
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinesterase, antioxidant activity and phytochemical investigation into aqueous extracts from five species of Agrimonia genus

Abstract: Aqueous extracts of aerial flowering parts of five Agrimonia species (Rosaceae): Agrimonia coreana Nakai, Agrimonia japonica (Miq.) Koidz, Agrimonia procera Wallr., Agrimonia eupatoria L. and Agrimonia leucantha Kunze were investigated on their antioxidant activity, measured using five different methods; the best was the extract from A. procera with IC50 values from 6 to 29 μg/mL. All the extracts displayed inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) at the tested concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…were able to inhibit the acetylcholine esterase [18,19]. Kubinova et al showed that an extract of A. procera (100 μg/mL) also displayed the inhibition of acetylcholine esterase [20]. Lee et al reported that an extract of Agrimonia eupatoria attenuated glutamate-induced oxidative stress in hippocampal cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…were able to inhibit the acetylcholine esterase [18,19]. Kubinova et al showed that an extract of A. procera (100 μg/mL) also displayed the inhibition of acetylcholine esterase [20]. Lee et al reported that an extract of Agrimonia eupatoria attenuated glutamate-induced oxidative stress in hippocampal cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…The aerial parts of Agrimonia pilosa were also listed in the Chinese Pharmacopoeia as a kind of haemostatic drug for treating urinary, respiratory, digestive system diseases, and various kinds of bleeding such as bloody dysentery (Xu et al 2005;Wang et al 2012a). Pharmacological studies showed that A. pilosa exhibits antihaemorrhagic, antioxidant, hepatoprotective, anticancer and α-glucosidase inhibitory activities (Kubínová et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The total flavonoid contents in the edible extracts decreased in the following order: methanolic (2.58 ± 0.7 mg QE/100 g DW), ethanolic (1.96 ± 0.3 mg QE/100 g DW), aqueous (1.51 ± 0.1 mg QE/100 g DW), and acetone (1.13 ± 0.5 mg QE/100 g DW). Similar results—i.e., that the content of flavonoids was more than ten times lower than the content of all polyphenols—were obtained by Kubinová [ 26 ]. Our results concerning polyphenols are supported by other authors who found different substances in Agrimonia eupatoria L. From a group of flavonoids, researchers have detected apigenin derivatives [ 25 ], such as isovitexin (apigenin 6-C-glucoside) [ 26 ]; luteolin derivatives [ 27 ]; quercetine derivatives, such as rutin (quercetine 3-O-rhamnoglucoside) [ 24 , 28 ]; and kaempferol derivatives, such as astragalin (kaempferol 3-O-glucoside) [ 29 ].…”
Section: Resultsmentioning
confidence: 91%
“…Similar results—i.e., that the content of flavonoids was more than ten times lower than the content of all polyphenols—were obtained by Kubinová [ 26 ]. Our results concerning polyphenols are supported by other authors who found different substances in Agrimonia eupatoria L. From a group of flavonoids, researchers have detected apigenin derivatives [ 25 ], such as isovitexin (apigenin 6-C-glucoside) [ 26 ]; luteolin derivatives [ 27 ]; quercetine derivatives, such as rutin (quercetine 3-O-rhamnoglucoside) [ 24 , 28 ]; and kaempferol derivatives, such as astragalin (kaempferol 3-O-glucoside) [ 29 ]. Condensed tannins, such as agrimoniin [ 23 ] and hydrolyzable tannin pedunculagin [ 27 ], were isolated.…”
Section: Resultsmentioning
confidence: 91%